2010
DOI: 10.1007/s10867-009-9184-6
|View full text |Cite
|
Sign up to set email alerts
|

Mean-squared atomic displacements in hydrated lysozyme, native and denatured

Abstract: We use elastic neutron scattering to demonstrate that a sharp increase in the mean-squared atomic displacements, commonly observed in hydrated proteins above 200 K and often referred to as the dynamical transition, is present in the hydrated state of both native and denatured lysozyme. A direct comparison of the native and denatured protein thus confirms that the presence of the transition in the mean-squared atomic displacements is not specific to biologically functional molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 51 publications
5
31
0
Order By: Relevance
“…For example, J. Pieper et al, in the case of hydrated Photosystem (PS) II, have demonstrated that the PDT occurs at the same temperature value at which the electron transport efficiency highly increases [12]; however, several exceptions exist [13][14][15]: e.g. in Ref.…”
mentioning
confidence: 99%
“…For example, J. Pieper et al, in the case of hydrated Photosystem (PS) II, have demonstrated that the PDT occurs at the same temperature value at which the electron transport efficiency highly increases [12]; however, several exceptions exist [13][14][15]: e.g. in Ref.…”
mentioning
confidence: 99%
“…Thus, we can expect that is also the same whether the biomolecule is native or denatured. This expectation is in accord with the results of elastic neutron scattering experiment by Mamontov et al [67] Before one can take these deviations seriously one should be mindful of the large error involved in determining dielectric relaxation data at high frequencies near 1 GHz (the upper limit of the frequency range of the spectrometer used), but the errors were not reported by the authors of [25].…”
Section: Same Dynamics Transition and T D In Both Hydrated Native Andsupporting
confidence: 82%
“…It should also be noted that in the nanosecond time scale used in the mentioned studies a significant contribution to the MSD of protein powders comes from methyl group rotations, and it masks changes in MSD that may result from unfolding. 26 We also remark that the degree of folding and exposure to water can vary significantly among different IDPs and proteins of varied unfolded content. 4 Consequently, the dynamical and mechanical properties of such proteins, as well as the coupling between protein and hydration water motions, 14 can change as a function of the compactness of the conformation.…”
Section: ■ Introductionmentioning
confidence: 79%